Toward Enteral Nutrition in the Treatment of Pediatric Crohn Disease in Canada: A Workshop to Identify Barriers and Enablers. Issue 7 (2015) - Van Limbergen, Johan; Haskett, Jennifer; Griffiths, Anne M; Critch, Jeff; Huynh, Hien; Ahmed, Najma; deBruyn, Jennifer C; Issenman, Robert; El-Matary, Wael; Walters, Thomas D; Kluthe, Cheryl; Roy, Marie-Eve; et al.
Abstract : The treatment armamentarium in pediatric Crohn disease (CD) is very similar to adult-onset CD with the notable exception of the use of exclusive enteral nutrition (EEN [the administration of a liquid formula diet while excluding normal diet]), which is used more frequently by pediatric gastroenterologists to induce remission. In pediatric CD, EEN is now recommended by the pediatric committee of the European Crohn's and Colitis Organisation and the European Society for Paediatric Gastroenterology Hepatology and Nutrition as a first-choice agent to induce remission, with remission rates in pediatric studies consistently >75%. To chart and address enablers and barriers of use of EEN in Canada, a workshop was held in September 2014 in Toronto (Ontario), inviting pediatric gastroenterologists, nurses and dietitians from most Canadian pediatric IBD centres as well as international faculty from the United States and Europe with particular research and clinical expertise in the dietary management of pediatric CD. Workshop participants ranked the exclusivity of enteral nutrition; the health care resources; and cost implications as the top three barriers to its use. Conversely, key enablers mentioned included: standardization and sharing of protocols for use of enteral nutrition; ensuring sufficient dietetic resources; and reducing the cost of EEN to the family (including advocacy for reimbursement by provincial ministries of health and private insurance companies). Herein, the authors report on the discussions during this workshop and list strategies to enhance the use of EEN as a treatment option in the treatment of pediatric CD in Canada.